Change management in large organisations smoking laws - a case study - Kyredis, Katrina; Breitenmoser, Kurt; Kyredis, Katrina; Hayward, Nick; Video Education Australasia (Australia : Video Education Australasia, 2008)
Large organisations only survive in today?s highly competitive environment if they have the ability to effectively deal with change. And, as changes go, they don?t come much bigger than recent smoking bans and ensuring challenges for the hospitality industry. In this dynamic program, we examine change, the internal and external forces behind it, the restraining forces that prevent it, change implementation and evaluation.
DVD format
Keywords: Organizational change -- Case studies; Organizational learning -- Case studies; Smoking -- Prevention -- Case studies